The Integrative Role of Digital Branding and Library Services in Enhancing Generation Z Engagement and Interest - Dwi Putri Aulia; Delight Chikara (Codex: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
The advancement of digital technology has driven the transformation of library services, shifting the focus from functional provision to user experience through digital branding. This study aims to analyze the integrative role of digital branding and library services in shaping Generation Z engagement and interest at the Library of UIN Raden Fatah Palembang. A qualitative approach with a case study design was employed, involving Generation Z students as research participants. Data were collected through interviews, observations, and documentation, and analyzed thematically through data reduction, categorization, and interpretation. The findings indicate that digital library services are widely utilized due to their accessibility and usefulness; however, user engagement remains primarily functional. Digital branding practices are still oriented toward information dissemination and have not fully developed into interactive and sustainable user experiences. In addition, the integration between digital branding and library services remains partial. This study concludes that strengthening user-centered digital branding strategies is essential to enhance Generation Z engagement and contributes both conceptually and practically to the development of digital-based library services